Integrative action research on enhancing work collaboration through internal organization improvements and coaching - Guerrero, Crescencio T. (Animo Repository, 2020)
This action research revolves on enhancing work collaboration within the Accounting and Budget Department of Far Eastern University, Incorporated. The issue, which was collaboratively identified by the researcher and his colleagues in the Department, primarily rooted from the recurring audit comment from the external auditors to further improve the accounting close process. Bits and pieces of ideas coming from comments of the collaborators, and observation and analysis of events and situations, were likewise noted: infrequency of meetings, further improvement of coordination and communication, reasonable and relevant task assignments, strengthening the sense of responsibility and accountability, and the need for more frequent performance evaluation and feedback. To address the identified issue, the first cycle focused on establishing a formal Work Plan that documents the internal organization improvements aimed at addressing the observed weaknesses in our Department’s internal organization. In the second cycle, we implemented an internal coaching initiative as a supplement to our Work Plan. This addresses the knowledge gap brought about by the changes and improvements in task assignments which is documented as part of our Work Plan. At the conclusion of this action research project, a usable knowledge on the importance of formalized plans and coaching has been established as a significant element to work collaboration, together with everyone’s trust with each other that creates that needed bond, especially for groups or organizations that are human capital intensive, like our Accounting and Budget Department. Moreover, analysis of events and situations, as experienced by the researcher, together with his collaborators, provides an exciting insight on how the issue was identified and the interventions are arrived at. Also, relevant published works from a vast collection of available literature has been cited and referred to for further appreciation of the knowledge embodied in this action research.